Sex and the single Savior : gender and sexuality in biblical interpretation - Martin, Dale B., 1954- (Louisville, Ky. : Westminster John Knox Press, 2006)
"Probing into numerous questions about gender and sexuality, Dale Martin delves into the biblical texts anew and unearths surprising findings. Avoiding preconceptions about ancient sexuality, he explores the ethics of desire and marriage and pays careful attention to the original meanings of words. For example, after a remarkably faithful reading of the scriptural texts, Martin concludes that our contemporary obsession with marriage - and the whole search for the "right" sexual relationships - is antithetical to the message of the gospel. In all of these essays, Martin argues for engaging Scripture in a way that goes beyond the standard historical-critical questions and the assumptions of textual agency in order to find a faith that has no foundations other than Jesus Christ."--BOOK JACKET.
Ch. 1. Introduction : the myth of textual agency -- Ch. 2. The rhetoric of biblical scholarship : a primer for critical reading of historical criticism -- Ch. 3. Arsenokoites and Malakos : meanings and consequences -- Ch. 4. Heterosexism and the interpretation of Romans 1:18-32 -- Ch. 5. Paul without passion : on Paul's rejection of desire in sex and marriage -- Ch. 6. The queer history of Galatians 3:28 : "no male and female" -- Ch. 7. Sex and the single savior -- Ch. 8. Familiar idolatry and the Christian case against marriage -- Ch. 9. The hermeneutics of divorce -- Ch. 10. Community-shaped scripture -- Ch. 11. Conclusion : the space of scripture, the risk of faith.
Includes bibliographical references (p. 241-257) and indexes.
Keywords: Bible -- Criticism, interpretation, etc; Sex -- Biblical teaching